Kahoot! Games Enhance Vocabulary Learning? - V. Katemba, Caroline; H. L. Tobing, Joshua; A. Putri, Talitha (Revija za elementarno izobraževanje, 2022)
Many educators are considering using online games for learning vocabulary. Among the existing online games is Kahoot. This study aimed to determine if male and female students learn vocabulary the same way using Kahoot! Games. The study examined whether there was any significant difference among the female and male groups in their vocabulary enhancement. This quantitative research study used a pre-test and a post-test administered to sixty-eight seventh-grade students. Findings revealed a significant difference in vocabulary enhancement between female and male students, thus supporting the use of Kahoot! games as an effective method for teaching vocabulary.
Keywords: technology & Vocabulary, Male vs. Female, smartphone, EFL context